Toxic-metal-induced alteration in miRNA expression profile as a proposed mechanism for disease development - Wallace, David R.; Taalab, Yasmeen M.; Heinze, Sarah (Cells, 2020)
Toxic metals are extensively found in the environment, households, and workplaces and contaminate food and drinking water. The crosstalk between environmental exposure to toxic metals and human diseases has been frequently described. The toxic mechanism of action was classically viewed as the ability to dysregulate the redox status, production of inflammatory mediators and alteration of mitochondrial function. Recently, growing evidence showed that heavy metals might exert their toxicity through microRNAs (miRNA)—short, single-stranded, noncoding molecules that function as positive/negative regulators of gene expression. Aberrant alteration of the endogenous miRNA has been directly implicated in various pathophysiological conditions and signaling pathways, consequently leading to different types of cancer and human diseases. Additionally, the gene-regulatory capacity of miRNAs is particularly valuable in the brain—a complex organ with neurons demonstrating a significant ability to adapt following environmental stimuli. Accordingly, dysregulated miRNAs identified in patients suffering from neurological diseases might serve as biomarkers for the earlier diagnosis and monitoring of disease progression. This review will greatly emphasize the effect of the toxic metals on human miRNA activities and how this contributes to progression of diseases such as cancer and neurodegenerative disorders (NDDs).
Gesehen am 14.09.2020